Investigating the Strength Properties of Concrete containing Construction & Demolition waste using Response Surface Methodology Techniques (RSM) - Oluyemi Ayibiowu, Bamitale Dorcas (European Journal of Applied Sciences, 2022)
The framework through which waste from Construction and Demolition activities could be reused in concrete was developed using the Response Surface Methodology techniques. An experimental design to determine the proportions of CDW waste which include Recycled Concrete Aggregate (RCA) and Recycled Fine Aggregate (RFA) to be mixed with other concrete constituents using Central Composite Design (C.C.D) orthogonal design was performed. Four factor variables which include %RCA to replace granite, Water-cement ratio, %RFA to replace river sand and RCA aggregate size was used while the response variable is the concrete compressive and flexural strength. Thirty (30) experimental runs were generated and conducted. The result was then analyzed using the RSM regression analysis. The result showed that %RCA showed the highest influence on both compressive and flexural strength of the CDW concrete. The Contour analysis also showed the behavior of the strength properties of CDW concrete to different variations of the factor variables. The research showed that the use of CD waste in concrete production help improve the properties of concrete.